2017
DOI: 10.3390/cryst7110333
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Phase Transformation in Single-Crystal Germanium during Single and Cyclic Nanoindentation

Abstract: Single-crystal germanium is a semiconductor material which shows complicated phase transformation under high pressure. In this study, new insight into the phase transformation of diamond-cubic germanium (dc-Ge) was attempted by controlled cyclic nanoindentation combined with Raman spectroscopic analysis. Phase transformation from dc-Ge to rhombohedral phase (r8-Ge) was experimentally confirmed for both single and cyclic nanoindentation under high loading/unloading rates. However, compared to single indentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…However, the Raman spectrum of indented Ge exhibits both a (dc-Ge) peak centered at ~301 cm −1 and an additional peak at ~202 cm −1 . This extra peak with other peaks position at 86 cm −1 , 94 cm −1 , 202 cm −1 , 225 cm −1 , and 249 cm −1 are identified to be linked to the presence of the r8 phase of Ge 24–27,43,44 . It was reported that unlike Si BC8 and R8 phases which coexist stably under ambient conditions, germanium phases R8 and BC8 are observed to transform to a hexagonal diamond phase under ambient pressure and temperature 23,43 .…”
Section: Resultsmentioning
confidence: 80%
“…However, the Raman spectrum of indented Ge exhibits both a (dc-Ge) peak centered at ~301 cm −1 and an additional peak at ~202 cm −1 . This extra peak with other peaks position at 86 cm −1 , 94 cm −1 , 202 cm −1 , 225 cm −1 , and 249 cm −1 are identified to be linked to the presence of the r8 phase of Ge 24–27,43,44 . It was reported that unlike Si BC8 and R8 phases which coexist stably under ambient conditions, germanium phases R8 and BC8 are observed to transform to a hexagonal diamond phase under ambient pressure and temperature 23,43 .…”
Section: Resultsmentioning
confidence: 80%
“…Global demand for germanium is expected to grow to 320 -400 tons annually by 2030, and production could increase by about one-and-a-half times, according to the US Geological Survey [32]. The cost of germanium single crystals, depending on their quality characteristics, can reach 10 -15 thousand dollars per kilogram [33]. Meanwhile, approximately 100 tons of germanium are lost each year during coal mining in Donbas, which is about 45% of the known total annual production of this metal in the world.…”
Section: The Choice Of Object To Studymentioning
confidence: 99%
“…However, most previous indentation studies focused on individual indentations, thus the effects of incremental-load cyclic loading/unloading still remains unknown. In recent years, cyclic indentation has been attempted on brittle singlecrystalline materials such as silicon [16,17] and germanium [18,19], and it was demonstrated that multi-cyclic indentation induced completely different mechanical responses from that of individual indentations. For optical glasses, multi-cyclic indentation tests were performed by using Vickers indenters [20] and spherical indenters [21] to investigate fatigue properties, and the evolution of indentation-induced cracks during cyclic bending tests was also investigated [22].…”
Section: Introductionmentioning
confidence: 99%